What Drives Investment Intention in Indonesia Stock Market during Pandemic? - Nabila Na'ma Aisa; Desiana Fitriani; Azizah Humairo (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
The pandemic has brought a massive change to the global economy. Stocks have been very volatile since last year. Despite the uncertainty in the capital market, retail investors have increased significantly. It depicts the great intention to invest in the capital market by individuals. In addition, the demography shows young people play a role in boosting new investors in Indonesia. The present study investigates the effect of subjective norms and risk perception on investment intention in the capital market. We collect the data from university students in Yogyakarta through an online questionnaire. After testing the validity and reliability of the data, a multiple regression analysis is conducted to test the data. Subjective norms and risk perception affect the intention to invest positively.